Age-Related Changes of Some Chemical Components in the Leaves of Oriental Beech (Fagus orientalis Lipsky.) - Turfan, Nezahat; Ayan, Sezgin; Nurten Yer, Esra; Özel, Halil Barış (Hrvatski Sumarski Institut (Croatian Forest Research), 2019)
Background and Purpose: This study presents the analysis of photosynthetic pigments, proline, total soluble protein, total amino acids, glucose, sucrose, total soluble sugars, total amount of phenolic compounds and flavonoids, malondialdehyde (MDA) and hydrogen peroxide (H2O2) concentration in the leaf samples collected from oriental beech trees, which are naturally spread in Kastamonu Province, Turkey, with differing ages, enzyme activities of ascorbate peroxidase (APX), catalase (CAT) and superoxide dismutase (SOD). Material and Methods: The research was carried out on oriental beech trees (Fagus orientalis L.) of different ages located at 1300 m high elevation in Ahlat Village of Kastamonu Province, Turkey. Oriental beech trees of different ages (≥25, ≥50, ≥100, ≥200 and ≥600 years-old) constituted the material of this study. In leaf samples taken from trees of different ages, photosynthetic pigments (chlorophyll a, chlorophyll b, total chlorophyll and carotenoid), proline, total soluble protein, total amino acid, glucose, sucrose, total soluble sugars, the amount of total phenolic compounds and flavonoids, MDA, H2O2 concentration, enzyme activities of APX, CAT and SOD, as well as the relationship between the total content of C, N and H elements and the tree ages were studied. Results: As a result of the research conducted, significant differences were determined in terms of chlorophyll, total phenolic compound, flavonoid, glucose, amounts of sucrose, nitrogenous compounds, proline, total soluble protein, MDA, H 2O2 concentrations, and the activities of APX, CAT and SOD in the leaves of oriental beech trees with differing ages. The highest content of chlorophyll a was found to be in the youngest age group of ≥25 years. Total chlorophyll is low in young trees and high in middle-aged, old and very old trees. According to the results obtained, it was concluded that the MDA and H2O2 concentrations in the trees did not vary depending on the age of trees only, but also on the genotype, environmental conditions and metabolic activities. It was concluded that the fact that the total chlorophyll, phenolic compounds and sucrose content in oriental beech trees are high and that MDA content is low could have an influence on the long life of ≥600 years-old oriental beech trees. Conclusions: The activity of photosynthesis is related to leaf characteristics more than the age of trees.
Keywords: Oriental Beech; tree physiology; Oriental beech; Enzyme Activities; Forestry; SD1-669.5; Tree Physiology; Chemical Content; enzyme activities; Tree Age; chemical content; tree age; 15. Life on land